The Impact of Freelancing on Work-Life Balance - Zarish Assad (International Journal of Global Sustainable Research, 2024)
This paper explores the impact of freelancing on work-life balance using a secondary data analysis research approach. The study utilizes a wide range of data sources, including industry data from freelancing platforms like Upwork, Fiverr, and Freelancer, global surveys such as the Freelancing in America report, and government labor statistics from the U.S. Bureau of Labor Statistics (BLS) and Eurostat. These data sources provide information on freelancers' demographics, income stability, working hours, and overall job satisfaction. The data selection focused on relevance, recency (within the past five years), and reliability, ensuring that credible and current information was used to assess the relationship between freelancing and work-life balance. Data analysis methods included descriptive, comparative, and correlation analysis, as well as thematic analysis to identify patterns and relationships between freelancers' professional activities and personal well-being. Findings from the study reveal varying degrees of work-life balance across different segments of the freelancing population, with factors like income stability, geographical location, and industry playing significant roles. While freelancing offers flexibility, challenges such as income instability and long working hours can negatively affect work-life balance. The results underscore the need for support systems to enhance freelancers' ability to manage their work and personal lives effectively..